Glassimations - Deakin University. Art Gallery; Torre, Lienors (Burwood, [Vic.] : Deakin University Art Gallery, 2012)
Glassimations, an exhibition of contemporary Australian artworks that bridge the materials of glass and animation to produce works with qualities that are unique to these two mediums and yet create a dialogue between them. The exhibition includes the work of a variety of artists. Lee Whitmore paints on glass to achieve an animated image that metamorphs with its own unique movement; Tom Moore animates his blown glass creations into their own world; Deirdre Feeney animates onto her glass architectural forms to produce places of light that condense time and are full of intangible narrative; Mark Eliott and Jack McGrath collaborate to bring their understanding and skills of glass and animation together, creating works that are founded in the production processes of both materials; and Lienors Torre and Alastair Boell collaborate to create animated films that become objects of glass and furniture, able to occupy real spaces in our domestic lives.
Curated by Lienors Torre.
Catalogue of exhibition held at Deakin University Art Gallery, 2 June to 14 July 2012.
Includes bibliographical references.
Keywords: Glass art -- Australia -- Exhibitions